Perencanaan Strategi Bisnis Usaha Online: UMKM - Fira Rosida; Indria Ikhtia Zahra; Meisha Farah Widyaningrum; Rusdi Hidayat Nugroho; Maharani Ikaningtyas (ManBiz: Journal of Management and Business, 2024)
The development of micro, small and medium enterprises (MSMEs) requires a joint role in the environment from both regulators and other companies. The Business Competition Supervisory Commission (KPPU) together with the Ministry of Cooperatives and SMEs signed a memorandum of understanding to form a task force to monitor partnerships established between SMEs and large industries. This article explores the programs organized by the Ministry of Cooperatives and Small and Medium Enterprises for the development of MSMEs. Through literature and online research about company programs, researchers can compare them with government policy programs to analyze the accuracy of expert programs. The research results show that the joint Business Competition Supervisory Commission (KPPU) program can fulfill the policies of the Ministry of Cooperatives and SMEs stipulated in the 2020-2024 Strategic Plan.